687 Timings of CT Scans in Suspected Renal Colic. (12th October 2021) - Sabaratnam, R; Callan, R; Baptiste, G; Miah, T; Sharaf, A; Chaudry, A
Abstract: Aim: Renal/ureteric colic is common; it has an annual incidence of 1-2 cases per 1000 people and has high recurrence rates. National Institute for Health and Care Excellence (NICE) guidelines recommend imaging within 24 hours of presentation for all patients with suspected renal or ureteric stones and, for most adults, a low-dose non-contrast computed tomography (CT) scan should be offered. We set out to assess adherence to this guidance within our centre. Method: We reviewed the records of patients presenting with suspected renal colic from December 2019, up to and including March 2020, in a single centre. We assessed the proportion of adult patients who underwent a CT within 24 hours. Results: The data from 95 patients aged 19-82 years was analysed. We found that 37(38.9%) patients did not receive a CT scan within 24 hours. 16(17%) patients waited over 1 week for a CT KUB. Conclusions: Our findings show a considerable proportion of patients who did not receive a CT within the first 24 hours of presenting with suspected renal/ureteric colic. This has led to plans for a formal clinical pathway to be established within out trust.